HUBUNGAN KOORDINASI MATA KAKI DAN KESEIMBANGAN DENGAN KEMAMPUAN SHOOTING MENGGUNAKAN PUNGGUNG KAKI PADA OLAHRAGA FUTSAL DI TIM FUTSAL SMA NEGERI 1 BUNGARAYA - Kusaini, Agus; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this research was to see the relationship between eye-to-foot coordination and balance with the ability to shoot using instep in futsal in the futsal team of SMA Negeri 1 Bungaraya. The research was conducted at SMA Negeri 1 Bungaraya, Bungaraya District, Siak Regency in November 2020 - March 2021. This research is classified as a type of correlational research. Given the total population of less than 100 people, the entire population was sampled (total sampling) as many as 15 people. Based on the results of the research conducted and the statistical data management process, it can be ignored that there is a relationship between ankle coordination and the ability to shoot using the instep, where rtab is at a significant level α (0.05) = 0.532 means rcount (0.958)> rtab (0.532 ). Then there is a relationship between balance and the ability to shoot using feet, where rtab is at the significant level α (0.05) = 0.532, meaning rcount (0.751)> rtab (0.532), and there is a joint relationship between ankle coordination and balance with The ability to shoot using the instep in futsal sports in the futsal team of SMAN 1 Bungaraya, Bungaraya District, Siak Regency, where rtab is at a significant level α (0.05) = 0.514, meaning Rhitung (0.967)> rtab (0.532). In other words, being approved by Ha is accepted.Key Words: Ankle Coordination, Balance, Instep Shooting, Futsal Sports